Gastropod in Mangrove and Seagrass of PentaduTimur Village - Wawan S Husa; Faizal Kasim; Sri Nuryatin Hamzah (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
This study aims to determine the condition of gastropod in the area of mangrove and seagrass in the waters of the District of Tilamuta Pentadu Timur village, Gorontalo province. This study was conducted in November 2015 to April 2016. The method used is the 1x1 m transect quadrant. Data analysis included diversity index, Frequency type and Gastropod Similarity Index Efipauna and Treefauna. The results showed that the mangrove ecosystem, has gastropod species Epifauna of 17 types and 15 types for Treefauna. While on seagrass, consists of nine types Epifauna and 6 types Treefauna. Gastropod diversity index value Epifauna on mangrove ecosystems are 0.55 and 0.70 whereas Treefaunaie on seagrass for gastropods Epifauna is 0.77 with a high diversity categories and Treefauna is 0.18 with a low diversity category. Sulcata terrebralia species has the highest value of the frequency of attendance either in mangrove and seagrass ecosystems. Gastropod similarity index in mangrove and seagrass ecosystems is 79% with a very similar category. Keywords: mangrove; seagrass; gastropod.